Distinctive Features of Faults for Use in Power Transformer Differential Protection - Glazyrin V.E.; Litvinov I.I. (Problems of the Regional Energetics)
The aim of the work is to study the change in instantaneous values of the differential current in power transformer differential protection circuits under conditions of magnetizing inrush when the unloaded transformer is energized and under conditions of a fault within the protection zone. Saturation of measuring current transformers during the transient process leads to distortion of signals in their secondary windings, which can cause a long delay in the disconnection of the protected object and the development of an accident in the power system if traditional protective algorithms are used. Taking into account the peculiarities of the change in the instantaneous values of the differential current while developing the protection algorithm makes it possible to recognize faults with maximum speed before the moment of the first saturation of electromagnetic current transformers and thus avoid a delay in the operation of the protection. For quick and correct recognition of a fault within the protection zone authors proposed to monitor the maximum value of the derivative of the differential current and the duration of its monotonous change from the moment of the onset of the transient process. This is because the monitored parameters in the emergency and normal operation of the power transformer can vary significantly. Application of traditional protection algorithms together with proposed methods allows increasing the speed of differential protection response in different operation modes of the power system. Mathematical simulation has been used to study the magnetizing inrush and short circuits within the protection zone.